Pengaruh Daya Tanggap Staf Hotel Terhadap Kepuasan Tamu Karantina di Hotel Best Western Plus Kemayoran - Putri, Inchi Yurana; Rustini, Rustini (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study is to aimed to identify the influence of hotel staff responsiveness on quarantine guest’ satisfaction at Best Western Plus Kemayoran Hotel. The background of this study is the increasing outbreak of the corona virus which has caused every citizen who is in another country unable to return to their country of origin before carrying out a quarantine that has been regulated by the government. This analysis was conducted by the independent variable, namely the responsiveness of the hotel staff and the dependent variable which is the guests’ satisfaction. The data used by the researchers were taken from the total population of 12,048 quarantine guests in 2021 which the researchers then counted using the Slovin formula, hence the sample used in this study was 100 guest respondents who carried out quarantine at Best Western Plus Kemayojran Hotel by distributing questionnaires using the simple random sampling method which were then processed using a validity test, reliability test, hypothesis test, variable descriptive analysis, normality test, R2 determinant test, and T test. The value of the coefficient of determination (R2) on the symbol R square with a value of 0.592 or 59,2%, the value of t count 11.917 > table 1.984 with these results it can be concluded that H0 is rejected and H1 is accepted and it indicates that the variable Hotel Staff Responsiveness (X) significantly influence Guests’ Satisfaction (Y).